(untitled) (Conferencea, 2024)
The issues of organizing inclusive education within the framework of the existing legal regulation seem to be one of the most difficult and confusing. Here, educational, administrative, budgetary and labor laws come together, which causes a lot of contradictions in relation to each other. In this article, we will try to explain in simple terms the most difficult issues that a teacher may encounter in the process of organizing an inclusive environment in an educational institution.